Students’ Difficulties in Comprehending English Reading Text at SMPN 2 Bangkinang Kota - aulia salma; idham saputra (Indonesian Journal of Integrated English Language Teaching, 2021)
This research aimed to know students' difficulties in comprehending English reading text at SMPN 2 Bangkinang Kota. The design of this research is quantitative research with the use of descriptive quantitative study which focused on one variable. The population of this research was the eighth grade of SMPN 2 Bangkinang Kota. The total population was  112 students. To select the sample, the researcher uses simple random sampling. There were 28 students as the sample. In collecting data, the researcher distributed the questionnaire to the respondents consist of 15 items and used the documentation of the students' final task made by the English teacher. The data was analyzed by using Scale Likert through SPSS.16. The result of data analysis showed the lowest percentage of categories students' difficulties. The research found students' difficulties in comprehending English reading text at SMPN 2 Bangkinang Kota.